Root recovery and elemental composition in a perennial grass as affected by soaking conditions. (24th September 2021) - Thivierge, Marie‐Noëlle; Royer, Isabelle; Halde, Caroline; Chantigny, Martin H.; Bélanger, Gilles; Lachance, Chantal; Lavergne, Stéphanie
Abstract: Roots of perennial grasses, with their fibrous architecture, are difficult to separate from the surrounding soil. We assessed the effect of five soaking solutions (sodium bicarbonate, sodium chloride, disodium ethylenediamine tetraacetic acid [disodium EDTA], distilled water, and sodium hexametaphosphate) and three soaking durations (15 min, 2 h, and 16 h) on root recovery and root elemental composition, with and without a mathematical correction for residual soil adhering to roots. Roots were collected by soil coring in a timothy ( Phleum pratense L.) sward on a loam soil. After soaking, roots were washed, digitized, and analyzed for elemental composition. Soaking duration did not affect root mass and length, but the 16‐h duration resulted in the lowest ash concentration (136.7 vs. 146.4 g kg –1 dry matter [DM] on average across shorter durations), indicating a lower contamination by soil. The greatest root recovery was obtained with sodium bicarbonate (0.118 vs. 0.101 g DM core –1 on average across other solutions). Sodium hexametaphosphate led to the lowest root ash and element concentrations but left a P residue on the roots. Distilled water did not impair root cell integrity and led to a similar root recovery as sodium chloride, disodium EDTA, and sodium hexametaphosphate. A mathematical correction improved the estimates of (a) root mass for all soaking solutions and (b) root elemental composition for elements with higher concentrations in soils than in roots. Soaking solutions should be chosen as a function of the study objectives because of the trade‐off between root recovery and contamination by adhering soil. Core Ideas: A 16‐h soaking duration leads to lower root ash concentration than shorter durations. Soaking in sodium bicarbonate allows for greater recovery of root mass and length. Soaking in sodium hexametaphosphate reduces root ash and element concentrations. Mathematical correction for soil adhering to roots improves estimates of root mass. Soaking solution results in trade‐off between root recovery and soil contamination.